“It Takes Two to Tango”: Role of Neglected Macrophage Manipulators Coronin 1 and Protein Kinase G in Mycobacterial Pathogenesis - Saha, Saradindu; Das, Payel; BoseDasgupta, Somdeb (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages being the connecting link between innate and adaptive immune system plays a crucial role in microbial antigen presentation and orchestrates the subsequent clearance of microorganisms. Microbial invasion of macrophages trigger a plethora of signaling cascades, which interact among them to generate a dynamically altered hostile environment, that ultimately leads to disruption of microbial pathogenesis. Paradoxically, Mycobacterium sp. exploits macrophage proteins such as Coronin 1, Calcineurin, LRG47, SOCS1, CISH, Gbp5 etc. and secretes virulence proteins such as PknG, PtpA, SapM, Eis etc. to hijack these intra-macrophage, signaling cascades and thereby develop its own niche. Coronin 1, being a cortical protein is transiently recruited to all mycobacteria containing phagosomes, but only pathogenic mycobacteria can retain it on the phagosome, to hinder its maturation. Additionally, mycobacterial infection linked secretion of virulence factor Protein Kinase G through its phosphorylation, manipulates several macrophage signaling pathways and thus promotes pathogenesis at various stages, form early infection to latency to granuloma formation. Here we discuss the present status of mycobacteria engaged Coronin 1-dependent signaling cascades and secreted PknG related sequence of events promoting mycobacterial pathogenesis. Current knowledge about these two proteins in context of macrophage signaling manipulation encompassing diverse mechanisms like calcium-calcineurin signaling, reduced proinflamtory cytokine secretion, cytoskeletal changes, and adaptation in acidic environment, which ultimately converge toward mycobacterial survival inside the macrophages has been discussed.